2024
DOI: 10.1186/s12964-024-01584-z
|View full text |Cite
|
Sign up to set email alerts
|

The protein composition of exosomes released by prostate cancer cells is distinctly regulated by androgen receptor-antagonists and -agonist to stimulate growth of target cells

Golnaz Atri Roozbahani,
Miriam Kokal-Ribaudo,
Mehdi Heidari Horestani
et al.

Abstract: Background Prostate cancer (PCa) is a prevalent malignancy in men worldwide, ranking as the second leading cause of cancer-related death in Western countries. Various PCa hormone therapies, such as androgen receptor (AR)-antagonists or supraphysiological androgen level (SAL) reduce cancer cell proliferation. However, treated cells may influence the growth of neighboring cells through secreted exosomes in the tumor microenvironment (TME). Here, the change of protein content of exosomes secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These exosomes subsequently promoted the growth of LNCaP cells, underscoring their potential tumour-promoting activity within the microenvironment. This study enhances our understanding of AR-regulated exosome secretion by AR-ligands and how their protein content can mediate tumour growth [ 54 ].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…These exosomes subsequently promoted the growth of LNCaP cells, underscoring their potential tumour-promoting activity within the microenvironment. This study enhances our understanding of AR-regulated exosome secretion by AR-ligands and how their protein content can mediate tumour growth [ 54 ].…”
Section: Introductionmentioning
confidence: 93%
“…However, the exact mechanism behind SAL’s repressing effects has not yet been described. In his talk, Prof. A. Baniahmad revealed that SAL can induce cellular senescence in CSPC and CRPC in preclinical PCa models to the same extent as antiandrogens [ 54 ]. Data from his research group showed that antiandrogens and SAL induce a tumour suppressive program by the p15/p16 – pRb – E2F1 – Cyclin D1 axis [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation